1988
DOI: 10.1017/s0003598x0007397x
|View full text |Cite
|
Sign up to set email alerts
|

The recent reconstruction of the Bush Barrow lozenge plate

Abstract: The paper by Ian Kinnes et al. in the March number published the gold objects from Bush Barrow, Wiltshire, examined the evidence for the original form of the large lozenge, and described its recent restoration into a domed profile. In this paper a different view is taken of evidence for the original form of the lozenge and of the wisdom of its recent transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Mechanical alterations of archaeological metals were even conducted into the late 20th century, as evidenced by the restoration of a gold lozenge plate from Bush Barrow (Kinnes et al . 1988; Shell and Robinson 1988). One large difference between the earlier aggressive treatments and those conducted after the 1970s is that the more recent treatments are largely well documented and clearly identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical alterations of archaeological metals were even conducted into the late 20th century, as evidenced by the restoration of a gold lozenge plate from Bush Barrow (Kinnes et al . 1988; Shell and Robinson 1988). One large difference between the earlier aggressive treatments and those conducted after the 1970s is that the more recent treatments are largely well documented and clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of other conservation treatments on stress relaxation require study, particularly some of the relatively aggressive approaches used earlier in the 20th century, such as 'superheated steam' cleaning, localized heat treatment using blow torches and high-temperature acid baths (Scott 2002). Mechanical alterations of archaeological metals were even conducted into the late 20th century, as evidenced by the restoration of a gold lozenge plate from Bush Barrow (Kinnes et al 1988;Shell and Robinson 1988). One large difference between the earlier aggressive treatments and those conducted after the 1970s is that the more recent treatments are largely well documented and clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction in that case was arrived at by a different process, namely its actual restoration by an experienced metalwork conservator -Ian MacIntyre -who had observed that there was slack metal within the lozenge frame of the object which was inconsistent with an original planar object. It has been since been argued that the slack metal might be the result of postdepositional 'stretching' of the sheet (Shell & Robinson 1988) and this possibility must be borne in mind, but as for the Clandon piece there was no evidence for irregular stretching or any damage to decorative features. The result of the restoration was unexpected at the time, but it quickly became clear that the Bush Barrow lozenge made much more sense as a domed form once other fancy ornamental gear of the Early Bronze Age in Wessex and beyond was taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its value for testing the shape of a deformed object through manipulation of a replica, the electrotype may alsoserve to preserve the distorted shape of an object that is to be reshaped. Shell & Robinson (1988: 2524 show how it has been possible to use an electrotype made in 1922 as the basis for a metrical analysis; this presumably utilizes the form of the lozenge that is nearest to its excavated state.…”
mentioning
confidence: 99%